Emerging organoid-based platforms to study salivary gland hypofunction - Yoojin Seo; Hyung-Sik Kim (Organoid, 2022)
Xerostomia is a pathologic condition of hyposalivation due to salivary gland (SG) dysfunction. Although xerostomia significantly affects the quality of patients’ life, there is no satisfactory treatment for this disease. Importantly, the senior population is more susceptible to xerostomia than younger individuals and the prevalence of the disease is much higher in elderly women than in men. However, the mechanisms underlying these clinical correlations have not yet been elucidated and further studies are required. Given that cell lines exhibiting saliva-producing abilities are not available, the generation and maturation of salivary gland organoids (SGOs) have been spotlighted as a modeling system to investigate the homeostasis of SG stem cells, as well as the pathophysiology of SGs in disease. In this review article, we will review the latest reports dealing with the generation and maturation of SGOs by defining the stem cells in SGs. We will also discuss the recent literature proposing strategies to model disease and regenerate damaged tissues.